Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Bengkel Sumber Agung Tlogomas (Studi Kasus Pada Konsumen Sumber Agung Tlogomas No.30 Malang) - Rano Yudho Prawiro; Rois Arifin; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
AbstactThis study aims to determine and analyze the effect of service quality which consists of reliability, responsiveness, assurance, empathy and tangible variables to the satisfaction of consumers in the Sumber Agung Tlogomas workshop silmutaneously and partially. The population in this study are Sumber Agung workshop consumers or consumers who have used Sumber Agung services. The number of samples obtained using Solvin calculations as many as 77 respondents using non-probability sampling method. The analytical method used in this research is descriptive analysis and multiple regression analysis using the SPSS 2.0 program. From the results of the study showed that the quality of service partially and simultaneously had a positive and significant effect on consumer satisfaction at Sumber Agung Workshop. Key words : Effect Of Service Quality On Customer Satisfaction